A Strategic Approach to Climate Change in the Philippines : An Assessment of Low-Carbon Interventions in the Transport and Power Sectors - Transport and Traffic Planners (TTPI) Inc.; CPI Energy Phils., Inc. (World Bank, Washington, DC, 2017)
Globally, the Philippines is a minor emitter of greenhouse gases (GHGs), but cost-effective mitigation present opportunities that should be captured, noting that the country is one of the signatory member states to the 1992 United Nations Framework Convention on Climate Change (UNFCCC) and its Kyoto Protocol. The country accounts for less than 0.3 percent of global GHG emissions in 2004.4 However, emissions are on the rise from both energy-use and land-use changes. Even if the absolute scale will remain small, there are increasing number of development projects under preparation, which offers opportunities for cost-effective mitigation and adaptation measures. The Philippine Government's response to the climate change challenge has been active institutionally noting the recent restructuring of the Presidential task force on climate change. However, a clear strategy and action plan are still lacking. The international donor community, including development partners such as the Asian Development Bank (ADB), the United Nations International Strategy for Disaster Reduction (ISDR), the Millennium Challenge Corporation (MCC), and the United Nations Development Program (UNDP), is actively engaged in addressing climate change in the Philippines. There are several initiatives on capacity building for GHG accounting, monitoring and reporting, for preparation of a second National Communication to the UNFCCC, governance, renewable energy, urban air quality management, and forest management. There are likewise several World Bank supported climate change-related activities, with nine active operations. These encompass primarily energy sector operations.